Reduced-order synchronization of time-delay chaotic systems with known and unknown parameters - Ahmad, Israr; Saaban, Azizan; Ibrahim, Adyda; Shahzad, Mohammad; Mossa Al-Sawalha, M. (Elsevier Ltd., 2016)
In this article, a novel robust nonlinear controller approach is focused to study theoretically, the reduced-order synchronization phenomena of two unrelated time-delayed chaoticsystems under the determined and unknown parameters. It is assumed that the two systems are perturbed by the bounded unstructured uncertainties and unknown external disturbance. Based on the Lyapunov–Krasovskii functional theory, a robust nonlinear synchronization controller is focused and a suitable Lyapunov functional is constructed so that they establish the globally asymptotical stability of the closed loop at the origin. Subsequently, suitable adaptive laws of unknown parameters are designed to identify the unknown parameters.Finally, the effectiveness of the proposed reduced-order synchronization approach is verified by numerical simulations. A brief comparison of the present study with prior works has been given.